The Executive regulation of law No. 10/2018 on The Rights of persons with disabilities = اللائحة التنفيذية لقانون حقوق الأشخاص ذوي الإعاقة. (2025)
Decree of the prime minister no. 2733 of the year 2018 promulgating the executive regulations of the law on the rights of persons with disabilities -- the executive regulations of the law on the rights of persons with disabilities قرار رئيس مجلس الوزراء رقم 2733 لسنة 2018 بإصدار اللائحة التنفيذية لقانون حقوق الاشخاص ذوى الاعاقة – مادة (1) فى تطبيق أحكام هذه اللائحة ، يقصد بالكلمات والعبارات التالية المعنى المبين قرين كل منها